The driving forces behind households' accumulation of consumer debt - Himal Gautam; Ella Getz Wold; Magnus A. H. Gulbrandsen; Plamen Nenov (Norges Bank, 2024)
In this Staff Memo we explore the determinants of unsecured consumer debt among Norwegian households using detailed administrative data from 2020 to 2024. We identify a set of key drivers, including life-cycle patterns, labor market shocks, and homeownership transitions. Our findings reveal that younger households, renters, and individuals with limited financial assets are more likely to rely on consumer loans. Homeownership reduces dependence on such debt through access to lower cost credit options, while unemployment increases reliance on unsecured loans for consumption smoothing. Our results highlight the interplay between financial vulnerability, life events, and debt composition, offering policy insights for promoting financial stability and mitigating household debt risks.
hdl:11250/3170202
Keywords: 330